Non-communicable diseases’ risk factors in India: a review of the current situation - Verma, Anjana; Patyal, Ashish; Mathur, Medha; Mathur, Navgeet; Virmani, Shiv (International Journal Of Community Medicine And Public Health, 2021)
Non-communicable diseases (NCDs) are responsible for considerable morbidity and mortality, leading to a significant burden on the health care systems in developing countries like India. Despite heavy burden, there is no regular system of collection of good quality representative data on NCDs or their risk factors in India. The published review articles show the trends of risk factors, however only for one or few more risk factors, thereby rendering them non comprehensive. This paper examines the updated data and epidemiology of all the NCD risk factors, to provide the summary estimates of their prevalence at national level. A thorough knowledge on current status of risk factors is required to formulate the policies and programmes, so that the rising burden of NCDs can be tackled.